Odpowiedzi

2009-12-09T20:11:27+01:00
A) x+(3x-y²+7)= x+3x-y²+7= 4x-y²+7
b) -a+(2a-3b-1)= -a+2a-3b-1= a- 3b+1
c) -x²+(x²-x-7)= -x²+x²-x-7= -x-7
d) -b³-(b³-b²-b)= -b³-b³+b²+b=-2b³+b²+b
e) (2a-3b)+(4a-b)= 2a-3b+4a-b= 6a-4b
f)-(x²-3x)+(x²+3x)= -x²+3x+x²+3x= 6x
g) (a+b-c)-(2a-b+2c)= a+b-c-2a+b-2c= -a+2b-3c
h) -(x²-xy-x)-(-x²+2xy+2z) = -x²+xy+x+-2xy-2z= x²-xy+x-2z


4 5 4
Najlepsza Odpowiedź!
2009-12-09T20:12:30+01:00
A)x+3x-y²+7= 4x-y²+7
b)-a+2a-3b-1= a-3b-1
c)-x²+x²-x-7= -x-7
d)-b³-b³+b²+b=-b (do potemgi 6) +b²+b
e)2a-3b+4a-b=6a-4b
f)-x²+3x+x²+3x= 6x
g)a+b-c-2a+b-2c= -a+2b -3c
h)-x²+xy+x+x²-2xy-2z=-xy+x-2z
4 5 4